Antiviral effect of triple helix-forming oligonucleotides on feline infectious peritonitis virus infection in vitro - Choong, Oi Kuan (2012)
Feline infectious peritonitis virus (FIPV) is a feline coronavirus (FCoV) which causes a fatal immune-mediated disease called feline infectious peritonitis (FIP) in cats. The virus is classified under the family Coronaviridae which consist of a positive sense single stranded RNA genome positioned in helical symmetry. FIPV has been proven as mutants of feline enteric coronavirus (FECV) where the main transmission route for this virus is through faecal-oral route which target the monocytes and macrophage cells. Antiviral chemotherapy treatments using Ribavirin and interferon have been used to treat the disease symptomatically. However, these treatments are not effective to control the fatal progression of the disease. Furthermore, the various vaccines that have been developed are ineffective to control FIP in cats. Hence, the development of new effective therapy against FIP is impelled. Triple Helix-Forming Oligonucleotide (TFO) were chosen as a potential anti-viral therapy to inhibit FIP replication due to its ability to compete successfully with other DNA/RNA binders and sequence-specific binding. Specific TFOs targeted to the selected regions of virulent feline coronavirus (FCoV) strain FIPV WSU 79-1146 genomes were designed and tested in FIPV infected Crandell-Reef Feline Kidney (CRFK) cell line. Five different circular TFOs (TFO1 to TFO5) and one unrelated circular TFO (TFO7) were designed and tested for in vitro antiviral effects. TFO1 and TFO2 target the 5’ and 3’ untranslated region (UTR) of FIPV genome,respectively, while the TFO3, TFO4 and TFO5 target the different regions of open reading frame (ORF) 1a/1b of FIPV genome. Results revealed that TFO1, TFO3, TFO4 and TFO5 were able to hybridize to the target regions and produced triplex, while TFO2 was unable to perform hybridization with its target region. In vitro antiviral assays were conducted to examine the ability of TFOs to inhibit virus replication in cell culture based on the presence of CPE and quantitation of viral RNA genome using qRT-PCR. Results from this study showed 50 to 100 nM of circular TFO1 is sufficient to inhibit virus replication. However,increasing the concentration of TFO1 to 500 nM does not enhance the ability of the TFO to inhibit FIPV replication. In the study of antiviral effect of TFOs, results showed the copies of viral RNA genome of cells treated with TFO1, TFO2, TFO3,TFO4, TFO5 and TFO7 are 3.65 x 109, 2.23 x 1014, 4.86 x 109, 5.01 x 109, 4.41 x 109 and 6.02 x 1014, respectively. Hence, transfection with all the circular TFOs, except for TFO2 significantly reduced viral RNA genome up to 100,000 fold compared to mock transfected cells. As expected the mock transfected cells showed high copy number of viral RNA genome, 3.93 x 1014. qRT-PCR study also showed that all linear TFOs and unrelated TFO7 were unable to show any antiviral properties towards the virus. In addition, circular TFO1 and TFO5 which effectively inhibit FIPV replication failed to show any antiviral properties in influenza virus subtype H1N1 infected cells. In conclusion, all the circular TFOs except for TFO2 demonstrated antiviral effect on FIPV replication indicating the potential use of TFO as an antiviral agent against coronavirus such as FIPV in cats. Further studies are underway to demonstrate the therapeutic values of the designed TFOs towards FIPV infection in cats.